Study on the Bearing Capacity and Engineering Performance of Aeolian Sand - Han Xia; Jingtao Zhang; Jun Cai; Huangsong Pan; Xuesen She (Advances in Materials Science and Engineering)
The climate in the aeolian desert has great differences from that in other regions, generally showing large diurnal temperature differences and extremely dry and low groundwater level characteristics. Therefore, the physical and mechanical characteristics of the sand are different from those of other regions, and it has a loose soil structure, large pores, and a low bearing capacity. To ensure the security and applicability of engineering, it is necessary to study the engineering characteristics of aeolian sand. This paper focuses on the bearing capacity parameters of aeolian sand in the Mu Us Desert, and test sites in 6 weak foundation areas are selected. Large numbers of basic soil mechanical parameters have been collected through in situ static load tests (SLT) and laboratory confined compaction tests (CCT) to evaluate the effect of foundation treatments. The results show that the characteristics of aeolian sand in the Mu Us Desert include low moisture, poor cohesion, and easy compaction. The mud and water content affect the bearing capacity of aeolian sand. For weak foundations, adding a geogrid or replacing a weak soil layer with stone and aeolian sand can significantly improve the bearing capacity.